2021
DOI: 10.3390/antibiotics10080992
|View full text |Cite
|
Sign up to set email alerts
|

Role of dipA and pilD in Francisella tularensis Susceptibility to Resazurin

Abstract: The phenoxazine dye resazurin exhibits bactericidal activity against the Gram-negative pathogens Francisella tularensis and Neisseria gonorrhoeae. One resazurin derivative, resorufin pentyl ether, significantly reduces vaginal colonization by Neisseria gonorrhoeae in a mouse model of infection. The narrow spectrum of bacteria susceptible to resazurin and its derivatives suggests these compounds have a novel mode of action. To identify potential targets of resazurin and mechanisms of resistance, we isolated mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…We previously showed the phenoxazine dye resazurin has antimicrobial activity against Francisella tularensis and N. gonorrhoeae [14][15][16]. Resazurin is produced from resorcinol (1,3-dihydroxybenzene), which is obtained by the distillation of Brazilwood extract.…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed the phenoxazine dye resazurin has antimicrobial activity against Francisella tularensis and N. gonorrhoeae [14][15][16]. Resazurin is produced from resorcinol (1,3-dihydroxybenzene), which is obtained by the distillation of Brazilwood extract.…”
Section: Introductionmentioning
confidence: 99%
“…This collection also gathers papers on antibiotic resistance of some of the major emerging infections pathogens such as Mycobacteroides abscessus [ 3 ], Klebsiella pneumoniae [ 4 , 5 ], Salmonella sp. [ 6 , 7 ], Francisella tularensis [ 8 ], Acinetobacter baumannii [ 9 , 10 ], or Pseudomonas aeruginosa [ 11 ] and other human pathogens such as Neisseria gonorrhoea [ 12 ], Staphylococcus aureus [ 13 ], or Escherichia coli [ 14 ]. Most of them are high-priority pathogens [ 15 ], according to the National Institute of Allergy and Infectious Diseases, and are globally and medically important pathogens.…”
mentioning
confidence: 99%
“…Souder et al have identified a novel role for two genes dipA and pilD in Francisella tularensis (the etiologic agent of Tularaemia) susceptibility to resazurin [ 8 ].…”
mentioning
confidence: 99%